The complete genome sequence of Eubacterium limosum SA11, a metabolically versatile rumen acetogen. Issue 1 (December 2016) - Kelly, William; Henderson, Gemma; Pacheco, Diana; Li, Dong; Reilly, Kerri; Naylor, Graham; Janssen, Peter; Attwood, Graeme; Altermann, Eric; Leahy, Sinead
Abstract Acetogens are a specialized group of anaerobic bacteria able to produce acetate from CO2 and H2 via the Wood–Ljungdahl pathway. In some gut environments acetogens can compete with methanogens for H2, and as a result rumen acetogens are of interest in the development of microbial approaches for methane mitigation. The acetogenEubacterium limosum SA11 was isolated from the rumen of a New Zealand sheep and its genome has been sequenced to examine its potential application in methane mitigation strategies, particularly in situations where hydrogenotrophic methanogens are inhibited resulting in increased H2 levels in the rumen. The 4.15 Mb chromosome of SA11 has an average G + C content of 47 %, and encodes 3805 protein-coding genes. There is a single prophage inserted in the chromosome, and several other gene clusters appear to have been acquired by horizontal transfer. These include genes for cell wall glycopolymers, a type VII secretion system, cell surface proteins and chemotaxis. SA11 is able to use a variety of organic substrates in addition to H2 /CO2, with acetate and butyrate as the principal fermentation end-products, and genes involved in these metabolic pathways have been identified. An unusual feature is the presence of 39 genes encoding trimethylamine methyltransferase family proteins, more than any other bacterial genome. Overall, SA11 is a metabolically versatile organism, but its ability to grow on such a wide range of substrates suggests it may not be a suitable candidate to take the place of hydrogen-utilizing methanogens in the rumen.